First report of Israeli acute paralysis virus in asymptomatic hives of Argentina - Reynaldi, Francisco José (2011)
Honey bee mortality has recently been associated with Israeli acute paralysis virus (IAPV), a proposed etiological agent for a new syndrome known as Colony Collapse Disorder. Bees infected with this virus show shivering wings, progress into paralysis, and finally die outside the hive. During the last years, honey bee mortality became a serious problem for Argentinean beekeepers. We herein report the preliminary results of a survey carried out to detect IAPV in samples taken from several Argentine provinces, by using a reverse transcription Polymerase Chain Reaction assay. Our data indicate the existence of high frequency of IAPV in asymptomatic hives of Argentina.